Teaching music through listening and project based learning - Hake, Samuel (Kansas State University, 2019)
My Master’s report will overview my music teaching techniques in Music Technology, my project-based course for 7th and 8th grade students. In this course’s second project, students create their own drum loops with a drum machine and match music loops to make a full sounding song. We utilize the music software “Reason” to introduce Basic song form, Intro/Outro, Melody, Bass Line, and Chordal support in project two. Students will do their best to match their drums with appropriate music loops or match their entire, 60 second song, to the drums they create. A development I’m excited to continue in my teaching for the future is readily teaching the “WHY.” I frequently teach in a hurry to convey as much information as possible but forget to give the students an exact reason or goal for each repetition. This has begun to transform many of the musicians I teach and provides greater comprehension every day I teach. Secondly the Master of Music coursework at Kansas State University has given me a new passion for my own philosophy of teaching music, through the main pillar of listening. Listening can provide students with feedback for self-knowledge in many musical and non-musical situations. This has provided many improvements in student behavior, my behavior, and our group cohesion. I now value teaching with this philosophy in mind because I’ve developed it myself through my coursework. It feels great to teach out of an authentic philosophy, and I’m excited to keep learning and molding what I do for each student.
Keywords: Listening; Project based learning; Instrumental music; Music technology